Governor's Residence - (:unkn) unknown (Goodwille and Wilson Ltd., Trinidad, 2009)
A picture showing a rear view of the Governor's residence with its Italian style arched doorways and Victorian style columns and railings and walls of local blue limestone. This residence was designated "The President's House" in 1976 when Trinidad and Tobago became a Republic.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Architecture--Trinidad and Tobago; President's House, The